Atezolizumab in early triple-negative breast cancer: the randomized phase 3 NSABP B-59/GeparDouze trial - Sibylle Loibl; Gong Tang; Valentina Nekljudova; Priya Rastogi; Sivaramakrishna Rachakonda; Mattea Reinisch; Joshua Acosta; Andreas Schneeweiss; Christie Hilton; Sabine Seiler; Rohit Bhargava; Thomas Karn; et al. (Nature Medicine, 2026)
Abstract Triple-negative breast cancer (TNBC) is an aggressive subtype with an activated tumor immune microenvironment. The multicenter, multinational, double-blinded NSABP B-59/GeparDouze trial evaluated the addition of atezolizumab (atezo) (773 patients randomized) or placebo (777 patients) to sequential taxane–carboplatin–anthracycline-based neoadjuvant chemotherapy in stage II–III TNBC. The addition of atezo did not significantly improve the primary endpoint of event-free survival (EFS) (HR, 0.80 (95% CI, 0.062–1.03); stratified log-rank P = 0.083, 4-year EFS rates difference 3.3%). The HR for overall survival was 0.86 (95% CI, 0.62–1.19), with a 4-year benefit of 0.7%. Prespecified subgroup analyses suggested heterogeneity in EFS, with benefit of atezo in patients presenting with clinical lymph node involvement ( P interaction = 0.039). Treatment-emergent adverse events with grades ≥3 were reported in 75.3% (atezo) versus 73.4% (placebo), and immune-related adverse events were reported in 27.6% (atezo) versus 11.4% (placebo). A total of 196 (25.5%) patients discontinued atezo and 143 (18.8%) patients discontinued placebo in the neoadjuvant phase. In an exploratory mRNA-based subset analysis, patients with basal-like immune-activated tumors may have benefited from atezo. TNBC subtyping to identify basal-like immune-activated tumors and quantification of tumor-infiltrating lymphocytes to identify tumors with high tumor-infiltrating lymphocyte counts could be a promising strategy to identify patients who benefit from the addition of immune checkpoint inhibitors to neoadjuvant chemotherapy. ClinicalTrials.gov registration: NCT03281954 .